Fatal code [large type] - Walters, Natalie, 1978- (Walters, Natalie, 1978- SNAP Agency, 2022)
"In 1964, a group of scientists called the Los Alamos Five came close to finishing a nuclear energy project for the United States government when they were abruptly disbanded. Now the granddaughter of one of those scientists, aerospace engineer Elinor Mitchell, discovers that she has highly sensitive information on the project in her possession -- and a target on her back. SNAP agent and former Navy cryptologist Kekoa Young is tasked with monitoring Elinor. This is both convenient since she's his neighbor in Washington, DC, and decidedly inconvenient because . . . well, he kind of likes her. As Elinor follows the clues her grandfather left behind to a top-secret nuclear project, Kekoa has no choice but to step in. And with danger closing in on all sides, Elinor will have to trust the man who has been spying on her to ensure her discoveries stay out of enemy hands -- and she stays alive."--